ANALISIS HUKUM TERHADAP PERAN DAN REGULASI PARALEGAL DALAM PERLINDUNGAN HAK MASYARAKAT ADAT DI INDONESIA - Collin Powel Hutabarat, Collin Powel Hutabarat; Martono Anggusti, Martono Anggusti (Judge : Jurnal Hukum, 2026)
This study examines whether paralegal efforts are effective in defending and protecting the human rights of indigenous communities, including their rights to land, natural resources, and cultural identity as recognised by national and international law. This study also examines how the livelihoods of these indigenous communities are preserved from generation to generation, ensuring their survival, through clear regulations guaranteeing customary land ownership, or decrees (SK) recognised by the government. Once a region obtains a decision, either at the district or provincial level, it will receive clear legal certainty regarding customary land ownership. Paralegals play a crucial role as a bridge between indigenous communities and the formal legal system, particularly in advocacy, legal assistance, and raising awareness of community rights. This study aims to analyse the forms of efforts and regulations that govern the role of paralegals in protecting the rights of indigenous communities. The research method used is a judicial normative approach with a regulatory approach and qualitative analysis of various regulations. Therefore, strengthening regulations and policies is necessary to expand the strategic role of paralegals in ensuring effective and sustainable protection of the rights of indigenous peoples.